Edaphic niche characterization of four Proteaceae reveals unique calcicole physiology linked to hyper‐endemism of Grevillea thelemanniana. Issue 3 (25th August 2020) - Gao, Jingwen; Wang, Feng; Ranathunge, Kosala; Arruda, André J.; Cawthray, Gregory R.; Clode, Peta L.; He, Xinhua; Leopold, Matthias; Roessner, Ute; Rupasinghe, Thusitha; Zhong, Hongtao; Lambers, Hans
Summary: Endemism and rarity have long intrigued scientists. We focused on a rare endemic and critically‐endangered species in a global biodiversity hotspot, Grevillea thelemanniana (Proteaceae). We carried out plant and soil analyses of four Proteaceae, including G. thelemanniana, and combined these with glasshouse studies. The analyses related to hydrology and plant water relations as well as soil nutrient concentrations and plant nutrition, with an emphasis on sodium (Na) and calcium (Ca). The local hydrology and matching plant traits related to water relations partially accounted for the distribution of the four Proteaceae. What determined the rarity of G. thelemanniana, however, was its accumulation of Ca. Despite much higher total Ca concentrations in the leaves of the rare G. thelemanniana than in the common Proteaceae, very few Ca crystals were detected in epidermal or mesophyll cells. Instead of crystals, G. thelemanniana epidermal cell vacuoles contained exceptionally high concentrations of noncrystalline Ca. Calcium ameliorated the negative effects of Na on the very salt‐sensitive G. thelemanniana . Most importantly, G. thelemanniana required high concentrations of Ca to balance a massively accumulated feeding‐deterrent carboxylate, trans ‐aconitate. This is the first example of a calcicole species accumulating and using Ca to balance accumulation of an antimetabolite.